The Positive Impact of Neurofeedback for Veterans With PTSD: Implications for Rehabilitation Counseling. - McReynolds, Connie J.; Yalamanchili, Priyanka (Journal of Applied Rehabilitation Counseling, 2021)
This article discusses positive therapeutic gains made with veterans whose primary treatment for post-traumatic stress disorder (PTSD) was cognitive rehabilitation using artifact corrected neurofeedback. Assessments at baseline and following 20 and 40 half-hour sessions of neurofeedback treatment identified significant improvements for auditory and visual attention using the Integrated Visual and Auditory Continuous Processing Test (IVA-2) and significant improvements in well-being based on the General Well-Being Scale (GWBS). Neurofeedback positively affected veteran's overall auditory attention with auditory test scores reflecting significant improvement following neurofeedback training sessions. Ratings of well-being significantly improved after treatment with 84% of the veterans improving five points or more on the GWBS. Improvements in well-being were found to be significantly correlated with increases in veterans' overall auditory attention and auditory processing speed. By identifying and improving auditory and visual processing difficulties in veterans with PTSD using neurofeedback, improvements in cognitive functioning may hold promise for enhanced employment outcomes.